O discurso de ódio, o silêncio e a violência: lidando com ideias odiosas - Mariana Oliveira de Sá (2020)
Freedom of expression is a substantial aspect of democracy. It contributes to the autonomy of individuals and to the development of society by fostering the free movement of ideas, thoughts and opinions. However, freedom of expression includes the possibility of its content having a hateful background, ideas that have a meaning of prejudice, discrimination, intolerance. Hate speech is configured as a practice that is directed to individuals or groups by virtue of characteristics such as race, ethnicity, nationality, religion, sexual orientation, sex, gender, physical condition. Thus, the idea of hate speech appears as a possible limitation of freedom of expression. In this context, this research assumes as a general objective to verify whether the prohibition of hate speech triggers the practice of violence against minority groups, rather than restraining them. The idea is to contribute to the development of the argument that the prohibition of hate speech can propitiate more hatred, denying the autonomy of individuals, their place of speech and their notion of equality, becoming an impulse to resist against what is different, eliminating it or disregarding it as equal. The contribution is made by an interdisciplinary bibliographical and documental research, in which studies in the areas of Law and Psychology were reconciled. It was possible to conclude that not all hate speech should be limited, but only that which may violate interests in an unfair way, which is capable of causing real and imminent danger of harm to another. Unlike this, hate speech should be tolerated. The results of the study also propose the possibility of intervention by the discourse itself, specifically through the technique of Non-Violent Communication, which allows hateful ideas to be said without damaging character.